IDNLearn.com provides a seamless experience for finding accurate answers. Find reliable solutions to your questions quickly and easily with help from our experienced experts.
If we know the quadratic formula, the quadratic formula is
x = [-b ± √(b²- 4ac)] / 2a
Gosh! So overwhelming! But let's look at the composition of a quadratic equation:
ax² + bx + c = 0
And we have 6x² - 3x = 1. So, what do we do? We need to put this quadratic equation into an easy form to find the value of a, b, and c to plug in to the equation.
We can just minus one on both sides to get this:
6x² - 3x - 1 = 0
Is it in the form of ax² + bx + c? Yes! a = 6, b = -3, and c = -1. Now, all we have to do is plug it into the quadratic formula.
x = [-b ± √(b²- 4ac)] / 2a
x = [-(-3) ± √((-3)²- 4(6)(-1))] / 2(6)
[3 ± √(9- 4(6)(-1))] / 12
[3 ± √(9 + 24)] / 12
[3 ± √(33)] / 12
At this point, we should just use a calculator, and recognize we have two answers because of the plus-or-minus sign! (or this sign: ±)
[3 ± √(33)] / 12
1) [3 + √(33)] / 12 = 0.73 approximately
2) [3 - √(33)] / 12 = -0.23 approximately
So, x=0.73 and x= -0.23.